Space-Time Line Code Aided Offset Spatial Modulation - Yashan Pang; Yue Xiao; Xia Lei; Yong Liang Guan; Jingon Joung (IEEE Access)
In this paper, a space-time line code (STLC) is combined with offset spatial modulation (OSM) for reaping both their advantages toward efficient multiple-input multiple-output (MIMO) transmission. Specifically, the spatial diversity offered by STLC increases the resilience against fading channels, while the simplified radio frequency (RF) switching processing merits of OSM inherently are preserved. As a further advancement in the pursuit of enhancing the performance of index detection, angle rotation is conceived and optimized for various transmit conditions. Subsequently, based on the approximation of the Q-function, an upper bound for the average bit error rate (BER) of STLC-OSM is derived in the context of an equispaced (ES) angle arrangement. Eventually, we demonstrate that STLC-OSM achieves considerable BER performance while achieving a unique single RF structure with a low implementation cost. Simulation results confirm the tightness of the derived BER bound and the advantages of the proposed scheme.